HIGH PRECISION FULLY INTEGRATED AIRBORNE DIGITAL MAPPING SYSTEMS – STATE OF THE ART AND PERFORMANCE ANALYSIS - M. M. R. Mostafa; J. Hutton; S. Sobol; L. Viveros; S. Cooper; Y. Raizman (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
This paper introduces the Phase One Aerial System 150, a next generation fully integrated fully digital aerial camera system with one single digital camera head and lens which almost matches the perfect geometry of a film camera for all airborne mapping applications. It is the first true replacement for the simplicity, geometry and efficiency established by film cameras for traditional airborne mapping. Several test flights were planned to be flown with the Phase One Aerial System 150 over the Greater Denver Area, Colorado, U.S.A. during the Winter of 2020. Two lenses are planned to be used, namely: 1) 50 mm lens for wide coverage and a geometry closest to that of a film camera which is suitable for most mapping applications, and 2) 90 mm lens which provides a higher resolution (smaller GSD) and a narrower field of view which is suitable for applications where less building lean might be required. Multiple flight altitudes are flown in order to end up with a GSD of 10 cm, and 20 cm, respectively. One dual-altitude flight was planned to characterize and calibrate the integrated system including camera in-flight calibration and camera/IMU boresight calibration. The remaining flights are planned to be used to validate system accuracy and productivity as well as the mapping product accuracy. Due to the Covid-19 pandemic and poor weather, only one full dual-altitude light has been flown. Therefore, system calibration, assessment, and validation are done using this single test flight. The remainder of the test flights intended for map production evaluation and accuracy assessment will be flown during the Spring of 2020, which results will be shared with the ISPRS audience during the congress presentations.